Análise da aplicação de estruturas Metassuperfície em antenas de microfita - Magno, José de Arimateia Pinto (2016)
The complexity of communication systems drives researches into new types of cheaper and more efficient antennas. Microstrip antennas are planar structures that can be used in various types of applications due to their peculiar characteristics. There are several techniques in the literature to improve the performance of these antennas, among them the use of metasurfaces. The working principle of these structures is similar to a metamaterial, based on constitutive properties, permissiveness and permeability, which are not found in materials in nature, resulting in a negative refractive index. The present work has the objective of analyzing the application of metasurfaces in planar antennas in the range of microwaves, in the frequencies of 1 to 10 GHz that comprise the bands L, S, C and part of band X, through the application of rectangular and circular SRR structures in the patch and ground plane of the antennas. The structures were divided into sizes λ/10, λ/15 and λ/20. The antennas were first analyzed by means of simulation with the commercial software HFSS®, with the simulated results were selected four antennas for manufacturing, of which the measured results of the parameters were obtained in a vector network analyzer, namely: loss of return, Gain and impedance matching. The results of the antennas manufactured were in agreement with the simulations